Epidemiological profile and hospitalization data of patients with inflammatory bowel disease - Brandão,Raphael Guilherme D’Angelis (2020)
Abstract Objective: This study's objective was to understand the epidemiologic profile of the patients with inflammatory bowel disease in the state of Tocantins, Brazil. Methods: This is a descriptive study of secondary data, which was gathered by using the Informatics Department of the Brazilian Health System, and it corresponds to the cases registered from January of 2010 to December of 2017. The data of interest were those related to the total number of admissions, age range, gender, ethnicity, city of hospitalization, and type of care. Results: There were 340 hospital admissions due to inflammatory bowel diseases in Tocantins, of which 204 (60%) were female patients and 136 (40%), male patients; the predominant age group was between 20 and 59 years old (65.88%). These hospitalizations lasted an average of 4.7 days and 98.23% of them occurred as a matter of urgency. Conclusion: The study demonstrated that the epidemiological profile of the inflammatory bowel disease in the state of Tocantins consists of female patients, aged between 20 and 59 years, with hospitalizations lasting 4.7 days and mainly urgent, demonstrating that it is necessary to implement screening measures in order to make the diagnosis earlier, thus preventing possible complications.